The development of a global LNG market : is it likely? If so, when? - Jensen, J (Oxford Institute for Energy Studies, 2004)
In its title, this study raises two questions: 'The Development of a Global LNG Market – Is it Likely? If So, When?' The answer to the first question must be, 'It depends on the definition of "global LNG market"'. But perhaps surprisingly, the answer to the second question – depending on the definition – might be, 'It is already here.' The reason the second answer may come as a surprise is that the global LNG market shows very little family resemblance to its two ostensible parents – the world oil market and the various liberalised onshore natural gas markets. But while it has clearly changed the traditional regional isolation of the gas industry and thus deserves recognition as a 'global market', it should not be expected to behave in the same way as either world oil or onshore gas.